ANALYSIS OF THE ATTORNEY GENERAL'S AUTHORITY IN CRIMINAL ECONOMIC LAW POLICY IN INDONESIA - Zainur Arifin Syah; Nandang Sambas; Chepi Ali Firman Zakaria; Dini Dewi Heniarti (RADJA PUBLIKA, 2025)
The Public Prosecutor's Office's authority to investigate economic crimes in Indonesia remains limited, both normatively and institutionally. Yet the complexity and magnitude of losses resulting from economic offenses demand an institution with adequate juridical and technical capabilities. To address issues concerning the legal basis for these limitations, their impact on law enforcement, and an ideal legal‐policy model for the Public Prosecutor's Office, a normative legal approach was employed, incorporating statutory, case‐law, historical, comparative, and conceptual analyses. The discussion examines the grounds for such limitations under positive law, the prevailing legal‐policy direction, and the design of criminal institutions, according to which the Public Prosecutor's Office may exercise investigative functions only where governed by a lex specialis provision. Moreover, the normative and practical effects of these limitations on enforcement effectiveness are analyzed, particularly in relation to inter-agency coordination, legal certainty, and public confidence. In light of the Public Prosecutor's Office's success in handling major corruption cases, which are part of the broader category of economic crimes, there is a pressing need to formulate a legal‐policy model to expand and strengthen the institution's role. As a solution, a criminal‐law reform model is proposed that positions the Public Prosecutor's Office as the principal investigative body through centralized authority, accountable procedures, and integrated cross‐agency governance. This model is intended to establish a more centralized, efficient, and credible system for enforcing economic criminal law while reinforcing the direction of national criminal-law reform.